Sistema de monitoreo de la significatividad de la educación salesiana en el Ecuador el PIES - Rodas Riera, Pablo Fernando (2008)
The present job belongs to a proposal of a system to do the monitoring of the purport of the Educational Salesian Centers of Ecuador from the Project Inspectorial of Salesian Education, which constitutes a necessity that demands an unpostponable answer. In first instance, the current thinking are collected in relation to the necessities and implications of the institutional evaluation, this permits us to understand the sense of the educational pastoral Salesian processes. Later all indicators of undertaking are described, than in agreement to the proposal of PIES they should be monitored with reference to their degree out of accomplishment and purport's level, in each of the strategies of PEPS of every CES of Ecuador, finally is described the fulfilled process for putting agreement jointly the criterions of judgment and establishing purport's levels of every indicator and the distributive proportion of every one in function of PEPS's strategies. The job is concluded with the detail of the technical filing cards that collect the referential information to each indicator and give a direction in the opinion of judgment; in the same way, it is proposes the matrix of monitoring with all the descriptors that it should be applied in each CES for the purport's judgment.